KEY ELEMENTS OF FORMING FUTURE MILITARY PILOTS' READINESS FOR THE INTERACTION DURING THE USE OF COMMON AIRSPACE IN THEIR PROFESSIONAL TRAINING - Malykhina, Ya.; A. , Bratslavska (Problems of Engineer-Pedagogical Education, 2021)
The article deals with the phenomena and the peculiarities of formation of future military pilots' professional readiness for professional interaction during the use of joint airspace with other countries. Nowadays the readiness of military aviation pilots to cooperate with their foreign-language counterparts in airspace outside Ukraine is at the forefront of scientific research, as it is the key to successful accomplishment by Ukrainian military pilots of relevant missions and effective cooperation with pilots and Air Traffic Controllers (Forward Air Controllers) from other countries as well as during taking part in joint exercises and peacekeeping operations. The scientific literature is analyzed and the concept of readiness of a person for an activity and a future pilot’s professional readiness for military activity is defined. It is established that military pilots' readiness for professional interaction while using common airspace ensures the pilot's ability to perform tasks in the common airspace. This kind of readiness is composed of a psychological component; cognitive component; operational component; personalityproductive component; and a language component that reflects the cadet's level of foreign language proficiency required for successful completion of their professional tasks. Increasing the level of the readiness requires from a future military pilot an adequate level of militaryspecific skills, psychological skills, and English proficiency at NATO STANAG 6001 Level 2 and ICAO Level 4. It is emphasized that the achievement by future military pilots of high level of readiness for professional interaction while using common airspace is the main task of the Aviation English Department of KhNAFU, which it successfully accomplished in cooperation with the military-special departments of the University and the Department of Military Psychology. For this purpose, a variety of advanced techniques and teaching methods such as simulator training on different types of aircraft (Mi-8, L-39, An-26 simulators) are used in the course of the future military pilots professional training.